Continuous production of power using microbial fuel cells with integrated biotrickling filter for ethyl acetate-contaminated air stream treatment. (21st December 2016) - Wu, Chih-Hung; Shih, Jing-Chen; Lin, Chi-Wen
Abstract: This work develops an innovative biotrickling filter-microbial fuel cell (BF-MFC) for use in electricity production and removing ethyl acetate (EA) that is emitted from a gaseous stream. A new membrane design, providing effective delivery of protons released from microorganisms that biodegrade EA from the anode to the cathode, was developed using a polyvinyl alcohol-membrane electrode assembly. As the EA concentration was increased from 0.18 g/m 3 to 1.44 g/m 3, the voltage increased from 49.4 mV to 658 mV, and when EA organic loading rate ranged from 14.41 to 29.58 g/m 3 /h, the elimination capacity (EC) reached almost the 100% conversion line. A maximum power density of 49.1 mW/m 2 and an EA elimination capacity of 83.8 g/m 3  h were obtained. Microbial community analysis revealed that two distinct groups of exoelectrogenic microbes and EA-degraders were dominated in the conductive coke surface and in the inner tube wall of the BF-MFC, respectively. Highlights: The novel BF-MFC simultaneously removes gaseous pollutants and generates electricity. Conductive cokes can form a three-dimensional electrode, increasing the reaction area of the anode. PVA-MEA effectively delivers protons from the anode to the cathode. BF-MFC promotes electron movement and thus is superior to the BF system.